Ekonomi dalam Perspektif Alquran - Zamakhsyari Abdul Majid (AHKAM : Jurnal Ilmu Syariah, 2016)
Economy in The Perspective of The Quran Alquran discuss economic problems because of it’s importance for human life. The level of economic development for human needs is very clear in the Alquran. This article examines the economic values in tafsir of Alquran viewpoints and problems, economic paradigms that are in society. Beginning from the problems in the economy legally up to the principles of economy, this article focuses on a theme and then this study uses a method known as tafsir mawdû’î. The economy based on the Alquran is the study of science that studies the problems of the economy by increasing the values of Islam in deep. The existences of Alquran on the economic development become an integral part of Muslims. The goals for all humans prosper in this world and hereafter and to enhance the physical and spiritual gratification in a balanced way, both individuals and groups.DOI: 10.15408/ajis.v16i2.4455